HCV-related cryoglobulinemic glomerulonephritis: implications of antiviral and immunosuppressive therapies - Garini, G.; Allegri, L.; Iannuzzella, et al., F. (Acta Biomedica Atenei Parmensis, 2007)
The most frequent renal involvement in patients with chronic hepatitis C virus (HCV) infection is cryoglobulinemic glomerulonephritis, with type I membranoproliferative glomerulonephritis (MPGN) being the predominant histological pattern. The pathogenesis of HCV-related cryoglobulinemic MPGN is unknown, but the glomerular damage may be due to the deposition of immune complexes of HCV, IgG, and IgM rheumatoid factors. Clinically, cryoglobulinemic MPGN may range from isolated proteinuria to overt nephritic or nephrotic syndrome, with variable progression to chronic renal insufficiency. The management of cryoglobulinemic MPGN is difficult; the eradication of HCV by means of antiviral therapy (peginterferon plus ribavirin) leads to clinical remission in a proportion of patients, but severe renal disease may be resistant to antiviral therapy. In such cases, corticosteroids and immunosuppressive agents have been used to decrease cryoglobulin production and improve the vasculitic manifestations, but long-lasting remission of the renal disease is uncommon. Here we describe four patients with HCV-related cryoglobulinemic MPGN and the strategies used for their management. The principal message provided by these illustrative cases is that antiviral therapy alone can be the first-line treatment for patients with mild-to-moderate kidney involvement, whereas a short-term course of corticosteroids and cytotoxic agents followed by antiviral therapy may be a reasonable therapeutic strategy for patients with severe/active renal disease.